Recovering Soil Quality of Elephant Grass-Cultivated Suboptimal Land Through Mycorrhizae and Organic Fertilizer - Fikrinda, Fikrinda; Khalidin, Khalidin; Arabia, Teti (KnE Life Sciences, 2022)
Bio and organic fertilizers have been used to improve soil quality for a long time in attempts to boost plant productivity. This field study used a randomized complete block design with three replications to investigate the effect of arbuscular mycorrhizal fungi with four doses (0, 15, 30, and 45 Mg Ha-1) of manure on the soil quality of elephant grass cultivated on suboptimal land. Mycorrhizae and manure improved the physical, chemical, and biological quality of the soil. Higher mycorrhizae-administered manure doses improved soil aggregate stability, pH, cation exchange capacity, organic carbon, total nitrogen, available phosphorous, exchangeable potassium, and the microbial population. Overall, the use of mycorrhizae and manure could aid in the recovery of suboptimal land quality. Keywords: aggregate stability; arbuscular; biofertilizer; manure; nutrient; carbon